2018
DOI: 10.5455/ajvs.278580
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Main Olfactory Bulb and Immunolocalisation of Brain-Derived Neurotrophic Factor in the Olfactory Layers of the African Grasscutter (Thryonomys swinderianus - Temminck, 1827)

Abstract: Key words:African grasscutter, Brain derived neurotrophic factor, Main olfactory bulb, Mitral cells, olfactory glomerulusThe present study has provided some novel findings on the structure of the olfactory bulb in the African grasscutter, by basic neuro-anatomical technique and immunhistochemical technique, using antibody specific to brain-derived neurotrophic factor. Brain samples extracted from neonates on postnatal day 3, juveniles on postnatal day 72 and adults on postnatal day 450 were utilised for the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…MOBs were obviously seen at ventrolateral and ventral brain views in dog and goat, respectively. These findings are similar to those described in a previously published study [24] that the adult African grass cutter olfactory bulbs were visible on the dorsal brain view but the elephant olfactory bulbs were hidden under the frontal lobes [25].…”
Section: Discussionsupporting
confidence: 91%
“…MOBs were obviously seen at ventrolateral and ventral brain views in dog and goat, respectively. These findings are similar to those described in a previously published study [24] that the adult African grass cutter olfactory bulbs were visible on the dorsal brain view but the elephant olfactory bulbs were hidden under the frontal lobes [25].…”
Section: Discussionsupporting
confidence: 91%
“…Gross morphological studies of the corpora quadrigemina [11], cerebellum [4,15] and olfactory bulbs [14] of the African grasscutter are available in extant literature. Conversely, no detailed account of the cerebrum and brainstem is available and the purpose of this article is to provide descriptive information to fill this gap.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the six layers Cytoarchitecture of the OB in the adult ASGS is in line with the findings of Olude et al (2014) in Africa giant rat (AGR). Conversely, 5 layers were reported in African grass cutter (Ibe et al, 2018) and four (4) layers in African giant rat (Nzalak et al, 2005). Comparatively, previous studies have also revealed up to eight (8) layers in Elephant and other vertebrates (Shoshani et al, 2006;Smitka et al, 2009) to include the ependymal layer and external granular layer.…”
Section: Discussionmentioning
confidence: 92%